N,S-GQDs / CoOOH nanocomposite and its preparation method and application
By using N,S-GQDs/CoOOH nanocomposites as fluorescence probes, the problem of insufficient detection sensitivity and selectivity of AA in the prior art is solved, high sensitivity and selectivity detection of AA is achieved, and low toxicity and good Biocompatibility.
Patent Information
- Application Number
- CN202210098801.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-27
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-01-27
AI Technical Summary
The prior art has problems of insufficient sensitivity and selectivity in detecting ascorbic acid (AA), and the application of nanomaterials is limited by problems such as poor light stability, low solubility and high toxicity.
Using N,S-GQDs/CoOOH nanocomposites as fluorescent probes, N,S-GQDs doped graphite phase carbon nitride quantum dots (N,S-GQDs) and cobalt oxygen hydroxide (CoOOH) are combined with chemical oxidation. Reducing the principle of fluorescence regulation can achieve high sensitivity and selective detection of AA.
It improves the sensitivity and selectivity of detecting AA, achieves low toxicity, good photostability and biocompatibility, and is suitable for in vitro and in vivo AA detection.
Smart Images

Figure CN114518345B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of analytical chemistry, and specifically relates to the construction of a N,S-GQDs / CoOOH fluorescent probe and its application in in vitro and in vivo ascorbic acid detection. Background Art
[0002] Vitamin C, also known as ascorbic acid (AA), is an antioxidant and one of the important vitamins for maintaining normal physiological functions of the body. Studies have shown that the content of AA in the human body is closely related to cardiovascular disease, arteriosclerosis, urinary tract stones, scurvy and many other diseases.
[0003] At present, the technologies and methods for detecting AA include fluorescence, high performance liquid chromatography (HPLC), capillary electrophoresis, enzyme-linked immunosorbent assay (ELISA), chemiluminescence and electrochemical analysis. Among these methods, high performance liquid chromatography has good accuracy and selectivity, but has high requirements for samples and expensive instruments; the material processing process of capillary electrophoresis is complicated, the procedures are cumbersome and time-consuming; ELISA has high requirements for instruments and equipment and liquid waste is difficult to handle; optical fiber chemical sensing requires professional personnel; chemiluminescence and electrochemical methods have simple instruments and short analysis time, but poor selectivity. Fluorescence analysis is a simple, rapid and highly sensitive detection method.
[0004] So far, nanomaterials such as organic fluorescent dyes, metal nanoclusters, two-dimensional nanosheets (CoOOH) and semiconductor quantum dots have been used to detect AA by fluorescence. However, the poor photostability of organic fluorescent dyes, the low solubility of CoOOH and semiconductor quantum dots, and the high toxicity of metal nanoclusters limit their application. Therefore, it is urgent to study a new fluorescent material with good eco-friendliness, good biocompatibility and high sensitivity to detect AA. Graphene quantum dots (GQDs), as a new type of promising fluorescent material, combine the excellent properties of graphene and quantum dots and have attracted widespread attention in the fields of chemical sensing, bioimaging and optoelectronic devices. How to improve the quantum yield of GQDs, improve the optical properties of GQDs, improve the sensitivity and selectivity of the detection method, and broaden its application in organisms are issues that need to be further addressed. Summary of the invention
[0005] The purpose of the present invention is to provide a N, S-GQDs / CoOOH nanocomposite and a preparation method and application thereof. The N, S-GQDs / CoOOH nanocomposite is used as a fluorescent probe to detect ascorbic acid (AA), further improving the sensitivity and selectivity of the detection method.
[0006] To achieve the above object, according to one aspect of the present invention, a N,S-GQDs / CoOOH nanocomposite is provided, comprising N,S-doped graphite phase carbon nitride quantum dots N,S-GQDs and cobalt oxyhydroxide CoOOH having fluorescence quenching effect.
[0007] Furthermore, the average particle size of the N,S-GQDs is 1-5 nm; the CoOOH is a hexagonal layered nanosheet with a size range of 75-85 nm. For example, the average particle size of the N,S-GQDs is 1.0 nm, 3.0 nm, 3.5 nm, 4.0 nm, 5.0 nm, and the size of the CoOOH is 75 nm, 80 nm, 85 nm.
[0008] According to another aspect of the present invention, a method for preparing the above-mentioned N,S-GQDs / CoOOH nanocomposite is provided, comprising the following steps:
[0009] Step 1, preparation of N, S-doped graphite phase carbon nitride quantum dots: citric acid and L-cysteine are mixed and heated to react, the obtained liquid is dissolved in ultrapure water, and the dialyzed solution is freeze-dried to obtain N, S-GQDs solid powder;
[0010] Step 2, preparation of CoOOH nanosheets: uniformly mix NaOH solution and CoCl2 solution, add NaClO solution dropwise to the mixed solution, and stir until no brown substance is regenerated in the solution; after ultrasonication of the obtained brown suspension, centrifuge it to obtain CoOOH nanosheets, and wash the obtained nanosheets with pure water for 2-3 times;
[0011] Step 3, preparation of N,S-GQDs / CoOOH nanocomposite: add N,S-GQDs solution to the CoOOH nanosheets prepared in step 2, mix and dilute with pure water, ultrasonically process the mixed solution to prepare N,S-GQDs / CoOOH nanocomposite solution, and freeze-dry the obtained nanocomposite solution to prepare N,S-GQDs / CoOOH nanocomposite solid powder.
[0012] Furthermore, in step 1, the mass ratio of the citric acid and L-cysteine in the reaction is 10:3.
[0013] Furthermore, the mass ratio of NaOH to CoCl2 is 164:1; and the ultrasonic time is 5-20 min.
[0014] Furthermore, in step three, the concentration of the CoOOH nanosheet aqueous solution is 10-60 μg / mL, for example, the concentration of the CoOOH nanosheet is 10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, 50 μg / mL, 60 μg / mL; and the ultrasonic time is 5-20 min.
[0015] According to another aspect of the present invention, there is provided a use of the above-mentioned N,S-GQDs / CoOOH nanocomposite in detecting ascorbic acid content and bioimaging.
[0016] Based on the N,S-GQDs / CoOOH nanocomposite of the present invention, the present invention provides a method for detecting the content of ascorbic acid AA, comprising the following steps:
[0017] Step 1: Dissolve the N,S-GQDs / CoOOH fluorescent probe solid powder into a buffer solution as a detection solution, mix it with AA standard solutions of different concentrations, measure the fluorescence intensity F0 of the detection solution before adding AA and the fluorescence intensity F of the detection system at different AA concentrations, calculate the relative fluorescence intensity 1 / (F-F0), use the AA concentration (1 / C) as the horizontal axis and the relative fluorescence intensity 1 / (F-F0) as the vertical axis, determine the relationship between AA concentration and relative fluorescence recovery intensity, and draw a standard curve;
[0018] Step 2: Mix the test solution and the AA sample of unknown concentration and record the fluorescence intensity;
[0019] Step 3: Obtain the AA content in the sample to be tested from the standard curve.
[0020] CoOOH can almost completely quench the fluorescence of N,S-GQDs through the fluorescence resonance energy transfer process. AA can reduce CoOOH to Co 2+ , so that N,S-GQDs fall off from CoOOH nanosheets and restore the fluorescence of the system. When the AA concentration ranges from 2.0 μM to 82.0 μM, 1 / C and 1 / (F-F0) have a good linear relationship (linear correlation coefficient R 2 The relative standard deviation (RSD) of the N,S-GQDs / CoOOH (0.7 mg / mL) solution was 3.20%, indicating that the method had good reproducibility and the fluorescent probe had high sensitivity and good selectivity.
[0021] The complex of the invention has low toxicity, good photostability and biocompatibility, and can be applied to in vitro and in vivo AA detection.
[0022] Based on the N,S-GQDs / CoOOH nanocomposite of the present invention, the present invention provides a method for detecting the content of ascorbic acid AA in cells using a fluorescent probe, comprising the following steps:
[0023] Step 1: Incubate the cells in an incubator with culture medium until the cells reach the logarithmic growth phase;
[0024] Step 2: Inoculate the cells in a 96-well plate and incubate, discard the culture medium, and incubate the cells with different concentrations of N,S-GQDs / CoOOH nanocomposites (0-250 μg / mL);
[0025] Step 3: Discard the supernatant and add MTT solution to each well to continue incubating the cells;
[0026] Step 4: Add dimethyl sulfoxide (DMSO) and shake; use a microplate reader to record the absorbance value of each well and measure the cytotoxicity of the N,S-GQDs / CoOOH nanocomplex.
[0027] Step 5: Inoculate the cells on a laser confocal dish and incubate for cell imaging;
[0028] Step 6: The first group of cells were incubated with culture medium as a control group; the second group of cells were incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes; the third group of cells were first incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes, and then AA was added to the dish for further incubation;
[0029] Step 7: The culture medium of the three groups of cells mentioned above must be discarded first, the cells must be rinsed with PBS buffer, and then fixed with paraformaldehyde, and the fluorescence images must be recorded using a laser confocal microscope.
[0030] Based on the N,S-GQDs / CoOOH nanocomposite of the present invention, the present invention provides a method for detecting ascorbic acid AA in zebrafish using a fluorescent probe, comprising the following steps:
[0031] Step 1: Incubate the fertilized zebrafish eggs, rinse them three times with culture medium, select well-developed embryos using an optical microscope, and evenly distribute them into two 6-well plates;
[0032] Step 2: Incubate zebrafish embryos with different concentrations of N,S-GQDs / CoOOH nanocomposites in the first 6-well plate, observe the number of surviving zebrafish, and calculate the survival rate;
[0033] Step 3: The second 6-well plate was incubated with zebrafish embryos containing different concentrations of N,S-GQDs / CoOOH nanocomposites, the body shape of the zebrafish was observed, and the deformity rate was calculated;
[0034] Step 4: The zebrafish were divided into three groups. The first group of zebrafish embryos were incubated with culture medium only as the control group; the second group of zebrafish embryos were incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes; the third group of zebrafish embryos were first incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes, and then incubated with culture medium containing different amounts of AA; after rinsing the well plate with distilled water, the fluorescence images of the three groups of zebrafish embryos were recorded using laser confocal microscopy.
[0035] The present invention relates to the construction of a graphite phase carbon nitride quantum dot composite fluorescent probe and its biological application. First, N, S doped graphite phase carbon nitride quantum dots (N, S-GQDs) were prepared, and the N, S-GQDs were combined with a nano quencher cobalt hydroxide to quench the fluorescence of the N, S-GQDs. Based on the principle of chemical redox regulation of fluorescence, a method for detecting ascorbic acid (AA) in vitro and in vivo was established. The probe preparation method is simple, the optical properties are stable, the sensitivity is high, and the biocompatibility is good, which is of great significance for studying the function of graphite phase carbon nitride quantum dots in vivo. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 (a) TEM image of CoOOH; (b) TEM image of N,S-GQDs / CoOOH nanocomposite;
[0037] Figure 2 is the X-ray diffraction spectrum of N,S-GQDs / CoOOH nanocomposite;
[0038] Figure 3 Fourier transform infrared spectrum of N,S-GQDs / CoOOH nanocomposite;
[0039] Figure 4 It is the XPS overall spectrum of N,S-GQDs / CoOOH nanocomposite;
[0040] Figure 5 The effect of different concentrations of AA on the fluorescence intensity of N,S-GQDs / CoOOH nanocomposites;
[0041] Figure 6 is the Lineweaver-Burk standard curve of fluorescence intensity and AA concentration of N,S-GQDs / CoOOH nanocomposite;
[0042] Figure 7Fluorescence imaging of N,S-GQDs / CoOOH nanocomposites to detect AA in MCF-7 cells; (ac) are bright field, dark field, and overlapping images of MCF-7 cells without N,S-GQDs / CoOOH nanocomposites treatment; (di) are bright field, dark field, and overlapping images of MCF-7 cells treated with N,S-GQDs / CoOOH nanocomposites; (go) are bright field, dark field, and overlapping images of MCF-7 cells treated with N,S-GQDs / CoOOH nanocomposites + AA (the excitation wavelengths of the blue and green channels are 405 nm and 488 nm, respectively);
[0043] Figure 8 Fluorescence imaging images of N,S-GQDs / CoOOH nanocomposites for detecting AA in zebrafish (ac) are bright field, dark field and overlapping images of zebrafish embryos without N,S-GQDs / CoOOH nanocomposites treatment; (di) are bright field, dark field and overlapping images of MCF-7 cells after treatment with N,S-GQDs / CoOOH nanocomposites; (gu) are bright field, dark field and overlapping images of zebrafish embryos after treatment with different concentrations of N,S-GQDs / CoOOH nanocomposites + AA (the excitation wavelengths of the blue and green channels are 405 nm and 488 nm, respectively). DETAILED DESCRIPTION
[0044] The technical scheme claimed in the present invention is further described below by some examples. The examples are used to explain the embodiments of the present invention and do not exceed the scope of the subject matter of the present invention. The protection scope of the present invention is not limited by the examples. Unless otherwise specified, the materials and reagents used in the present invention can be obtained from commercial products in the field.
[0045] Example 1: Synthesis of N,S-GQDs / CoOOH Nanocomposites
[0046] Preparation of N,S-GQDs: 1.0 g of citric acid and 0.3 g of L-cysteine were mixed and added to a 25 mL round-bottom flask. The mixture was heated to 240°C in a heating mantle for 10 min. The reactant liquefied and its color changed from white to light yellow and finally to orange. The obtained liquid was dissolved in 10 mL of ultrapure water and dialyzed in ultrapure water for 8 h using a dialysis membrane (1000 Da). The dialyzed solution was freeze-dried to obtain N,S-GQDs solid powder.
[0047] Synthesis of CoOOH nanosheets: NaOH solution (200 μL, 0.8 M) and CoCl2 solution (3 mL, 10 mM) were uniformly mixed, and NaClO solution (200 μL, 0.2 M) was added dropwise to the mixed solution, and stirred until no brown substance was regenerated in the solution. The obtained brown suspension was ultrasonicated for 10 min, and then centrifuged in a centrifuge at 4000 r / min for 20 min to obtain CoOOH nanosheets, and finally the obtained nanosheets were washed with pure water 2-3 times. The average particle size of N,S-GQDs is 3.5 nm, and the size of CoOOH is 80 nm.
[0048] Synthesis of N,S-GQDs / CoOOH Nanocomposites:
[0049] 100 μL of N,S-GQDs solution was added to the above-prepared CoOOH nanosheet aqueous solution (30 μg / mL), and diluted to 15 mL with purified water. The mixture was ultrasonicated for 10 min to obtain a N,S-GQDs / CoOOH nanocomposite solution. The obtained solution was freeze-dried to obtain a N,S-GQDs / CoOOH nanocomposite solid powder for subsequent experiments.
[0050] Figure 1 (a) is the TEM image of CoOOH, (b) is the TEM image of N,S-GQDs / CoOOH nanocomposite, and the inset is the enlarged TEM image of N,S-GQDs / CoOOH nanocomposite. Figure 2 The XRD patterns of N,S-GQDs, CoOOH and N,S-GQDs / CoOOH nanocomposites are shown in Figure 2. The FT-IR patterns and XPS patterns of N,S-GQDs, CoOOH and N,S-GQDs / CoOOH nanocomposites are shown in Figure 3. Figure 3 and Figure 4 .
[0051] Example 2: Synthesis of N,S-GQDs / CoOOH Nanocomposites
[0052] The synthesis of N,S-GQDs and CoOOH nanosheets was the same as in Example 1. The average particle size of N,S-GQDs was 3.5 nm, and the size of CoOOH was 80 nm.
[0053] Synthesis of N,S-GQDs / CoOOH nanocomposite: 100 μL of N,S-GQDs solution was added to the prepared CoOOH nanosheet aqueous solution (10 μg / mL) and diluted to 15 mL with purified water. The mixture was ultrasonicated for 10 min to obtain the N,S-GQDs / CoOOH nanocomposite solution. The obtained solution was freeze-dried to obtain the N,S-GQDs / CoOOH nanocomposite solid powder for subsequent experiments.
[0054] Example 3: Synthesis of N,S-GQDs / CoOOH Nanocomposites
[0055] The synthesis of N,S-GQDs and CoOOH nanosheets was the same as in Example 1. The average particle size of N,S-GQDs was 3.5 nm, and the size of CoOOH was 80 nm.
[0056] Synthesis of N,S-GQDs / CoOOH nanocomposite: 100 μL of N,S-GQDs solution was added to the prepared CoOOH nanosheet aqueous solution (60 μg / mL) and diluted to 15 mL with purified water. The mixture was ultrasonicated for 10 min to obtain the N,S-GQDs / CoOOH nanocomposite solution. The obtained solution was freeze-dried to obtain the N,S-GQDs / CoOOH nanocomposite solid powder for subsequent experiments.
[0057] Example 4: Detection of AA by fluorescence spectroscopy
[0058] The N,S-GQDs / CoOOH nanocomposite obtained in Example 1 was used as a detection solution, which was mixed with AA standard solutions of different concentrations to measure the fluorescence intensity F0 of the detection solution before adding AA and the fluorescence intensity F( Figure 5 ), calculate the relative fluorescence intensity 1 / (F-F0), take the AA concentration (1 / C) as the horizontal axis and the relative fluorescence intensity 1 / (F-F0) as the vertical axis, and determine the relationship between the AA concentration and the relative fluorescence recovery intensity ( Figure 6 ). When the AA concentration increased from 2.0 μM to 82.0 μM, 1 / C and 1 / (F-F0) had a good linear relationship (linear correlation coefficient R 2 The relative standard deviation (RSD) of the solution of N,S-GQDs / CoOOH (0.7 mg / mL) was 3.20% after 11 repeated determinations, indicating that the method had good reproducibility.
[0059] Example 5: Detection of AA in serum
[0060] The plasma and acetonitrile were mixed and shaken at a volume ratio of 1:1. After standing for about 3 minutes, the mixture was centrifuged at 4000 r / min for 15 minutes, and the supernatant was taken and filtered with a microporous membrane (0.45 μm). The blood sample was diluted 100 times with PBS (pH=7.4, 10 mM) buffer solution before use. The N,S-GQDs / CoOOH nanocomposite detection solution of the same concentration was divided into three parts, and an equal volume of 10.0 μM, 45.0 μM, and 80.0 μM AA standard solution was added to each part. The fluorescence intensity of the mixed solution was recorded, and the measured AA content was obtained from the standard curve. Compared with the concentration of the standard solution, the spiked recovery of AA was between 96.0% and 98.4% (Table 1). The experimental results show that this strategy can be used to detect AA in serum.
[0061] Table 1 Results of the recovery experiment of AA in serum
[0062]
[0063] Embodiment 6:
[0064] Detection of AA in orange juice: Take a certain amount of orange juice, filter the mixture with a separatory funnel, centrifuge the collected filtrate at 4000 rpm / min for 20 min, obtain the supernatant, and filter it through a microporous filter membrane (0.22 m). Finally, dilute the filtrate 600 times with PBS (pH=7.4, 10mM) buffer solution to determine the content of AA in orange juice. The N,S-GQDs / CoOOH nanocomposite detection solution of the same concentration was divided into three parts, and an equal volume of 10.0 μM, 45.0 μM, and 80.0 μM AA standard solution was added to each part. The fluorescence intensity of the mixed solution was recorded, and the measured AA content was obtained from the standard curve. The spike recovery rate was calculated by the following formula. The spike recovery rate of AA was between 99.0% and 101.5% (Table 2). The experimental results show that this strategy can be used to detect AA in serum.
[0065] Spike recovery (%) =
[0066] Where K0, K1, and K2 represent the detected amount, spiked concentration, and actual measurement, respectively.
[0067] Table 2 Experimental results of recovery rate of AA in orange juice
[0068]
[0069] Embodiment 7:
[0070] Application of cell imaging: MCF-7 (human breast cancer cells) cells were incubated in a 37°C, 5% CO2 incubator with 1640 medium containing 10% fetal bovine serum (FBS) and 1% penicillin-streptomycin. MCF-7 cells were seeded on laser confocal dishes for cell imaging. The grouping and specific incubation steps of MCF-7 cells were as follows: the first group of MCF-7 cells were incubated with 1640 medium for 4 h, which served as the control group; the second group of MCF-7 cells were incubated with 1640 medium containing 50 μg / mL N,S-GQDs / CoOOH nanocomplexes for 4 h; the third group of MCF-7 cells were first incubated with 1640 medium containing 50 μg / mL N,S-GQDs / CoOOH nanocomplexes for 4 h, and then 40 μM AA was added to the dish and incubated for 1 h. The cells in the three groups above all had to discard the culture medium, rinse three times with PBS buffer, and then fix with paraformaldehyde for 10 min. Then, the fluorescence images were recorded with a laser confocal microscope at 405 nm and 488 nm excitation wavelengths. Figure 7 As shown, it is demonstrated that N,S-GQDs / CoOOH nanocomposites can be applied to cell imaging and can identify AA in cells.
[0071] Embodiment 8:
[0072] Application of in vivo imaging in zebrafish: The in vivo imaging process of zebrafish is to divide the embryos into three groups. One group of zebrafish embryos was incubated with E3 culture medium only for 10 hours as a control group. The second group of zebrafish embryos was incubated with E3 culture medium (pH=6.0) containing 90 μg / mL N,S-GQDs / CoOOH nanocomplexes for 10 hours; the third group of zebrafish embryos was first incubated with E3 culture medium containing 90 μg / mL N,S-GQDs / CoOOH nanocomplexes, and the culture medium was discarded after 10 hours and incubated with E3 culture medium containing different amounts of AA (50 μM and 100 μM) for 1 hour. Wash three times with double distilled water before laser confocal imaging, place the zebrafish on a slide with a disposable pipette, and finally record the fluorescence images of the three groups of zebrafish embryos under 405nm and 488 nm excitation wavelengths using a microscope. The results are shown in Figure 8 As shown, it is shown that N,S-GQDs / CoOOH nanocomposites can recognize AA in biological systems.
[0073] Comparative Example 1: CoOOH nanosheets alone have no fluorescence and cannot be used for fluorescence detection of AA.
[0074] Comparative Example 2: N,S-GQDs and AA (10 -2 M) After mixing, the fluorescence intensity of N,S-GQDs remained basically unchanged, indicating that N,S-GQDs alone cannot be used for AA detection.
Claims
1. Application of N,S-GQDs / CoOOH nanocomposite in detecting ascorbic acid, wherein the N,S-GQDs / CoOOH nanocomposite comprises N,S-doped graphite phase carbon nitride quantum dots N,S-GQDs and cobalt hydroxide CoOOH with fluorescence quenching effect; the average particle size of the N,S-GQDs is 1-5 nm; the CoOOH is a hexagonal layered nanosheet with a size range of 75-85 nm; The preparation method of the N,S-GQDs / CoOOH nanocomposite comprises the following steps: Step 1, preparation of N, S-doped graphite phase carbon nitride quantum dots: citric acid and L-cysteine are mixed and heated for reaction, and the mass ratio of citric acid and L-cysteine for reaction is 10:3; the obtained liquid is dissolved in ultrapure water, and the dialyzed solution is freeze-dried to obtain N, S-GQDs solid powder; Step 2, preparation of CoOOH nanosheets: uniformly mix NaOH solution and CoCl2 solution, the mass ratio of NaOH to CoCl2 is 164:1, then add NaClO solution dropwise to the mixed solution, and stir until no brown substance is regenerated in the solution; ultrasonicate the obtained brown suspension for 5-20 min, and then centrifuge it to obtain CoOOH nanosheets, wash the obtained nanosheets with pure water for 2-3 times, and obtain a CoOOH nanosheet aqueous solution with a concentration of 10-60 μg / mL; Step 3, preparation of N,S-GQDs / CoOOH nanocomposite: add N,S-GQDs solution to the aqueous solution of CoOOH nanosheets prepared in step 2, mix and dilute with pure water, and ultrasonically prepare N,S-GQDs / CoOOH nanocomposite solution by ultrasonication for 5-20 min; the obtained nanocomposite solution is freeze-dried to prepare N,S-GQDs / CoOOH nanocomposite solid powder.
2. The use according to claim 1, characterized in that: The detection of ascorbic acid comprises the following steps: Step 1: Dissolve the N,S-GQDs / CoOOH nanocomposite solid powder in a buffer solution as a detection solution, mix it with ascorbic acid standard solutions of different concentrations, measure the fluorescence intensity F0 of the detection solution before adding ascorbic acid and the fluorescence intensity F of the detection system at different ascorbic acid concentrations, calculate the relative fluorescence intensity 1 / (F-F0), use the ascorbic acid concentration (1 / C) as the horizontal coordinate and the relative fluorescence intensity 1 / (F-F0) as the vertical coordinate, determine the relationship between the ascorbic acid concentration and the relative fluorescence recovery intensity, and draw a standard curve; Step 2: Mix the test solution and the ascorbic acid sample of unknown concentration and record the fluorescence intensity; Step 3: Obtain the content of ascorbic acid in the sample to be tested from the standard curve.
3. The use according to claim 1, characterized in that: The detection of ascorbic acid comprises the following steps: Step 1: Incubate the cells in an incubator with culture medium until the cells reach the logarithmic growth phase; Step 2: Inoculate the cells in a 96-well plate and incubate, discard the culture medium, and incubate the cells with N,S-GQDs / CoOOH nanocomposites containing different concentrations; Step 3: Discard the supernatant and add MTT solution to each well to continue incubating the cells; Step 4: Add dimethyl sulfoxide (DMSO) and shake; record the absorbance value of each well with a microplate reader to determine the cytotoxicity of the N,S-GQDs / CoOOH nanocomposite; Step 5: Inoculate the cells on a laser confocal dish and incubate for cell imaging; Step 6: The first group of cells were incubated with culture medium as a control group; the second group of cells were incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes; the third group of cells were first incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes, and then ascorbic acid was added to the dish for further incubation; Step 7: The culture medium of the three groups of cells mentioned above must be discarded first, the cells must be rinsed with PBS buffer, and then fixed with paraformaldehyde, and the fluorescence images must be recorded using a laser confocal microscope.
4. The use according to claim 1, characterized in that: The detection of ascorbic acid comprises the following steps: Step 1: Incubate the fertilized zebrafish eggs, rinse them three times with culture medium, select well-developed embryos using an optical microscope, and evenly distribute them into two 6-well plates; Step 2: Incubate zebrafish embryos with different concentrations of N,S-GQDs / CoOOH nanocomposites in the first 6-well plate, observe the number of surviving zebrafish, and calculate the survival rate; Step 3: The second 6-well plate was incubated with zebrafish embryos containing different concentrations of N,S-GQDs / CoOOH nanocomposites, the body shape of the zebrafish was observed, and the deformity rate was calculated; Step 4: Divide the zebrafish into three groups. The first group of zebrafish embryos were incubated with culture medium only as the control group; the second group of zebrafish embryos were incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes; the third group of zebrafish embryos were first incubated with culture medium containing N,S-GQDs / CoOOH nanocomplexes, and then incubated with culture medium containing different amounts of ascorbic acid; after rinsing the well plate with distilled water, the fluorescence images of the three groups of zebrafish embryos were recorded using laser confocal microscopy.